2018
DOI: 10.1159/000494970
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Vocal Tract Acoustics following Wendler’s Glottoplasty

Abstract: Purpose: To investigate the formant frequency (FF) features of transgender females’ (TFs) voice after Wendler’s glottoplasty surgery and compare these levels with age-matched healthy males and females. Study Design: Controlled prospective. Methods: 20 TFs and 20 genetically male and female age-matched healthy controls were enrolled in the study. The fundamental frequency (F0) and FFs F1–F4 were obtained from TF speakers 6 months after surgery. These levels were compared with those of healthy controls. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
0
3
0
18
Order By: Relevance
“…Their scores increased progressively and were slightly lower compared to the mean scores of the listening panel. In the study of Paltura et al [35], individuals reported that their voice did not sufficiently project femininity after glottoplasty. The authors recommended voice therapy as a possible approach to achieve a satisfactory feminine voice.…”
Section: Discussionmentioning
confidence: 99%
“…Their scores increased progressively and were slightly lower compared to the mean scores of the listening panel. In the study of Paltura et al [35], individuals reported that their voice did not sufficiently project femininity after glottoplasty. The authors recommended voice therapy as a possible approach to achieve a satisfactory feminine voice.…”
Section: Discussionmentioning
confidence: 99%
“…One exercise for one technique such as lip spreading and the cork exercise during this study might not be sufficient to detect substantial differences in these acoustic data. In contrast to Paltura and Yelken [83], the current study extracted the vowels from running speech, rather than performing acoustic analyses on isolated vowels.…”
Section: Discussionmentioning
confidence: 99%
“…Показанием для НГ являются андрофония у женщин при эндокринопатиях и побочных эффектах при приеме гормональных препаратов, а также паралич перстнещитовидной мышцы, при последнем дополнительно используют медиализацию голосовой складки. Сужение динамического диапазона рассматривается как желаемый эффект при НЛ, так как слабый голос ассоциируется с женским [9][10][11].…”
Section: хирургическое лечениеunclassified
“…Большинство авторов рекомендуют голосовую терапию с целью достижения удовлетворительного звучания в женском диапазоне [9,36], некоторые считают ее даже обязательной в виде «сэндвич терапии» -до и после хирургического лечения -с целью улучшения качества и характеристик женского голоса [12]. К сожалению, немногие исследователи подробно описали этапы голосовой терапии, хотя и указали на положительную динамику.…”
Section: фонопедияunclassified